2020
DOI: 10.3390/foods9081059
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fermentation and Phytase Treatment of Pea-Oat Protein Blend on Physicochemical, Sensory, and Nutritional Properties of Extruded Meat Analogs

Abstract: Plant materials that are used for the production of extruded meat analogs are often nutritionally incomplete and also contain antinutrients, thus there is a need to explore alternative plant proteins and pre-treatments. This study demonstrates application of phytase and fermentation to a pea-oat protein blend with a good essential amino acid profile and subsequent texturization using extrusion cooking. Enzymatic treatment reduced the content of antinutrient phytic acid by 32%. Extrusion also degraded phytic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 58 publications
(77 reference statements)
0
51
0
Order By: Relevance
“…The low-moisture extrusion process was carried out by the KETSE 20/40 twin-screw extruder (Brabender GmbH, Duisburg, Germany). The screw configuration was the same as that reported in Kaleda et al [14], set to impart high shear. A total of four protein mixes where used for the production of meat analogues: (I) P DF _O P : (70:30 w/w); (II) P Is _O P : (70:30 w/w); (III) P DF _P Is _O P : (35:35:30 w/w/w); (IV) S is_ O P : (70:30 w/w).…”
Section: Extrusion Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The low-moisture extrusion process was carried out by the KETSE 20/40 twin-screw extruder (Brabender GmbH, Duisburg, Germany). The screw configuration was the same as that reported in Kaleda et al [14], set to impart high shear. A total of four protein mixes where used for the production of meat analogues: (I) P DF _O P : (70:30 w/w); (II) P Is _O P : (70:30 w/w); (III) P DF _P Is _O P : (35:35:30 w/w/w); (IV) S is_ O P : (70:30 w/w).…”
Section: Extrusion Processmentioning
confidence: 99%
“…The raw materials for texturization are typically protein isolates derived from soy [10] and pea [7], but interest is rising for other protein sources, such as lupin [11], hemp [12], mung bean, and wheat gluten [13]. Recently, a pea-oat protein blend has been utilized to produce extruded meat analogues characterized by good amounts of essential amino acids and nutritionally valuable composition [14]. Moreover, extrusion cooking significantly reduces the antinutritional factors contained in pulses, enhancing the nutritional value [15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that similar fibrous structures can be made from soy and pea protein isolates as well as wheat gluten [ 11 , 12 , 13 ]. In addition, oat and pea protein blends have been used to produce fibrillar structures using a twin-screw extruder without cooling die [ 14 , 15 ]. For example, De angelis et al [ 15 ] produced meat analogs from an oat and pea protein isolate blend (ratio 30:70 w/w %) using low-moisture extrusion with parameters such as a screw speed of 600 rpm and an extrusion temperature of 150 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Products based on a fermented pea-oat protein blend were rated as dry and easily disintegrating. The low sensory moisture content of the fermented product obtained from pea and oat was confirmed by its low water holding capacity [ 67 ]. In fermented bio-yoghurt containing chickpea flour, the activity of LAB contributed to an increase in viscosity [ 68 ].…”
Section: Literature Reviewmentioning
confidence: 99%